2018
DOI: 10.1002/tea.21453
|View full text |Cite
|
Sign up to set email alerts
|

Students' understanding of the nature and purpose of models

Abstract: The process of thinking in and about models as a scientific practice should be integrated into science teaching and learning. Empirical studies show that students see models primarily in their role as media to facilitate content learning while rarely appreciating models as instruments of scientists which allow the deduction and the testing of predictions. In order to foster students' meta-modeling knowledge successfully, specific diagnostic information about students' understanding of models and modeling is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 61 publications
0
30
0
1
Order By: Relevance
“…Results revealed that most students who started their science learning with a preconception of models in the daily language perceptive and strived to move to the scientific language perceptive did not satisfactorily succeed. In contrast to the studies of Grosslight et al (1991) and Gogolin and Krüger (2018) in which they based their levelling of their subjects' understanding of models not only on how they see its representation but also on its function, this research further divided the model perceptions of students and teachers into three levels based on the representations of model, which allowed this research to reveal students' and teachers' understanding toward models in a more fundamental manner. Furthermore, the present study identified that a big portion of students and teachers are in the second level or the transitional perspective stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results revealed that most students who started their science learning with a preconception of models in the daily language perceptive and strived to move to the scientific language perceptive did not satisfactorily succeed. In contrast to the studies of Grosslight et al (1991) and Gogolin and Krüger (2018) in which they based their levelling of their subjects' understanding of models not only on how they see its representation but also on its function, this research further divided the model perceptions of students and teachers into three levels based on the representations of model, which allowed this research to reveal students' and teachers' understanding toward models in a more fundamental manner. Furthermore, the present study identified that a big portion of students and teachers are in the second level or the transitional perspective stage.…”
Section: Discussionmentioning
confidence: 99%
“…Students who responded with not sure or agree were regarded as having an incorrect concept of a scientific model, which constituted a large portion of the participants. On the other hand, Gogolin and Krüger (2018) proposed a five-aspect framework of model competence, and from those, the aspect of the nature of scientific models, as the most relevant to this research, had three levels: 1) a model is a replication of the original, 2) a model is an idealised representation of the original and 3) a model is a theoretical reconstruction of the original. Moreover, they found that a majority of the students in all grades (10, 11 and 12) see scientific models as an idealised representation of the original (level 2).…”
Section: Students' Model Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, models can be evaluated or changed according to how well they serve their intended purpose and there may be multiple models for a given phenomenon because they serve distinct purposes. Though the dimensions of nature and purpose of models clearly hold value for the science education research community (Crawford & Cullin, ; Grosslight et al, ; Grünkorn et al, ; Schwarz & White, ), we do not discuss them here in part because these dimensions have been well‐explored by other scholars (e.g., Gogolin & Krüger, ; Schwarz et al, ), and because we see them as intertwined with the four dimensions specified.…”
Section: Methodsmentioning
confidence: 99%
“…In the current project, the construct of interest is students' metamodeling knowledge, that is, students' epistemic knowledge of models and modeling. The literature contains descriptions of several dimensions of metamodeling knowledge, including the nature of models, the purpose of models, model changeability, model multiplicity, the evaluation of models, and the process of modeling (Crawford & Cullin, ; Gogolin & Krüger, , ; Grosslight et al, ; Grünkorn et al, ; Justi & Gilbert, ; Krell et al, ; Krell & Krüger, , ; Schwarz & White, ; Van Der Valk, Van Driel, & De Vos, ). Researchers have described metamodeling knowledge as multidimensional and have examined several specific dimensions including model multiplicity, model changeability, model evaluation, and the process of modeling.…”
Section: Literature Backgroundmentioning
confidence: 99%